Primary Liver Tumors in Turkey - Sebati ÖZDEMİR; Teoman SOSYAL; Hakan ŞENTÜRK; Muzaffer BEZGAL; Abdullah SONSUZ; Süha GÖKSEL; Perihan AKIN; Muzaffer GÜRAKAR (Turkish Journal of Gastroenterology, 2020)
-